Patterns of Expression and Normalized Levels of the Five Arabidopsis Phytochromes - Sharrock, Robert A. (American Society of Plant Physiologists, 2002)
Using monoclonal antibodies specific for each apoprotein and full-length purified apoprotein standards, the levels of the five Arabidopsis phytochromes and their patterns of expression in seedlings and mature plants and under different light conditions have been characterized. Phytochrome levels are normalized to the DNA content of the various tissue extracts to approximate normalization to the number of cells in the tissue. One phytochrome, phytochrome A, is highly light labile. The other four phytochromes are much more light stable, although among these, phytochromes B and C are reduced 4- to 5-fold in red- or white-light-grown seedlings compared with dark-grown seedlings. The total amount of extractable phytochrome is 23-fold lower in light-grown than dark-grown tissues, and the percent ratios of the five phytochromes, A:B:C:D:E, are measured as 85:10:2:1.5:1.5 in etiolated seedlings and 5:40:15:15:25 in seedlings grown in continuous white light. The four light-stable phytochromes are present at nearly unchanging levels throughout the course of development of mature rosette and reproductive-stage plants and are present in leaves, stems, roots, and flowers. Phytochrome protein expression patterns over the course of seed germination and under diurnal and circadian light cycles are also characterized. Little cycling in response to photoperiod is observed, and this very low amplitude cycling of some phytochrome proteins is out of phase with previously reported cycling of PHY mRNA levels. These studies indicate that, with the exception of phytochrome A, the family of phytochrome photoreceptors in Arabidopsis constitutes a quite stable and very broadly distributed array of sensory molecules.